(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
Legal and philosophical theories divide jurists. A comprehensive method seems to be needed in order to attain cohesion and to integrate jurisprudence. This essay offers an overlook on the general empirical method of the outstanding canadian contemporary philosopher Bernard Lonergan. It constitutes a serious approach to the basic structure of knowledge, that according to Lonergan, is conformed by four levels of concience and their interactions. The method´s characteristics enable positivism, rationalism, natural law, american realism and other philosophical conceptions on law to share common views. The “insight” or second level of concience is illustrated with an Agatha Christie´s story. Examples of modes of reasoning and intellectual inquiry of judges and the way they reach their conclusions are also provided.